PENGARUH PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) TERHADAP KEMAMPUAN PENALARAN SISWA SEKOLAH DASAR - Linda Astriani; Anggie Yulianti; Dendi Wijaya Saputra; Muhamad Sofian Hadi (Jurnal Holistika, 2023)
This study aims to determine how much influence the Indonesian Realistic Mathematics Learning (PMRI) approach has on mathematical reasoning skills at SDN Pondok Labu 12 Pagi South Jakarta. The method used uses an experimental model. The sampling technique uses purposive sampling with an experimental class of 32 students and a control class of students The instrument used is an essay test of 10 questions. The average calculation results of reasoning ability include 6 indicators with a percentage of 51.3% of the experimental class using the Indonesian Realistic Mathematics Education (PMRI) approach and the control class with a conventional approach of 43.37%. Then obtained a posttest value of the experimental class of 91.25 while the control class was 74.719 with a percentage of comparison of 65% n-gain value and obtained a tcount test of 8.931 greater than ttable of 2.657 (tcount = 8.931 > ttable = 2.657). So the conclusion in this study is that classes with the use of the Indonesian Realistic Mathematics Education (PMRI) model are higher than classes that learn through conventional learning.